Retraction: Nedeljković M, Kartelija G, Radenović L. Modification of the acetylcholine-induced current of the snail Helix pomatia L. by fast temperature changes. Arch. Biol. Sci. 2005;57(3):181-7, DOI: 10.2298/ABS0503181N - Editorial (Archives of Biological Sciences, 2015)
This is a notice of retraction of the article: Modification of the acetylcholine-induced current of the snail Helix pomatia L. by fast temperature changes, published in the Archives of Biological Sciences in 2005, Vol. 57, Issue 3. The Editor-in-Chief has been informed that this paper plagiarizes an earlier paper: Nedeljkovic M, Kartelija G, Radenovic L, Todorovic N. The effect of cooling on the acetylcholine-induced current of identified Helix pomatia Br Neuron. J Comp Physiol A. 2005;191(5):445-60. This claim is correct and the entire paper, except the abstract, is a verbatim copy of the earlier one. After confirmation of this fact, the Editor-in-Chief of the Archives of Biological Sciences has decided to retract the paper immediately. We apologize to the readers of the journal that it took so many years to notice this error and to retract the paper. We request readers of the journal to directly get in touch with the editorial office and the editors of the journal for similar cases in the future, so that they can be handled promptly. Link to the retracted article 10.2298/ABS0503181N